Perlindungan Hukum Peserta Program Jaminan Hari Tua pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan atas Penunggakan Pembayaran Iuran oleh Pemberi Kerja - Agara, Andryawan Perdana Dista; Santoso, Budi; Puspitawati, Dhiana (Universitas Negeri Malang, 2021)
The research objectives were to analyze the legal protection of participants of the old age guarantee program as well as the threat of sanctions for companies that delinquent payment of Social Security Agency for Employe (BPJS Employment) dues. The research used a juridical-sociological approach with a type of sociolegal research. Data sources in the form of primary, secondary, and tertiary data were analyzed qualitatively. Legal protection of participants of the old age guarantee program consisted of preventive legal protection, namely through Government Regulation Number 60 of 2015, and repressive legal protection based on internal Standard Operating Procedure (SOP) from BPJS Employment provided if the company in question delinquent dues payment. The threat of sanctions for companies that delinquent payment of BPJS Employment dues was in the form of administrative sanctions, although in practice the sanctions were considered ineffective to be applied.